2020
DOI: 10.1177/1751143720966280
|View full text |Cite
|
Sign up to set email alerts
|

The use of social media and online communications in times of pandemic COVID-19

Abstract: The use of social media as a tool for professional communication and education in healthcare has been increasing; pros and cons of such platforms were extensively debated in recent years with mixed results. During the COVID-19 pandemic, social media use has accelerated to the point of becoming a ubiquitous part of modern healthcare systems. As with any tool in healthcare, its risks and benefits need to be carefully considered. In this article, we review the use of social media in the current pandemic. Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(179 citation statements)
references
References 4 publications
3
168
0
8
Order By: Relevance
“…The study's findings depict that social media's use during the breakout of COVID-19 increased significantly compared to periods before. These findings concur with the findings of study [40], which revealed that the use of social media increased significantly in the healthcare sector as they needed to avail information and facts to the public fast and effectively. Even though the study focused more on social media use in the healthcare sector, it agrees with the current study that social media use increased significantly over the years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study's findings depict that social media's use during the breakout of COVID-19 increased significantly compared to periods before. These findings concur with the findings of study [40], which revealed that the use of social media increased significantly in the healthcare sector as they needed to avail information and facts to the public fast and effectively. Even though the study focused more on social media use in the healthcare sector, it agrees with the current study that social media use increased significantly over the years.…”
Section: Discussionsupporting
confidence: 90%
“…Comparing the results for the number of hours used in social media before and after COVID-19, we realize that after the pandemic broke out, people committed most of their time to social media to get news about the deadly disease called Covid-19 [40]. Before COVID-19, only 8.9% used social media for more than 8 hours; with the pandemic, this figure increased almost thrice to a tune of 25% (Figure 6).…”
Section: Figure 2 Worldwide Population Size Aware Of Covid-19mentioning
confidence: 98%
“…Indeed, in the media today, we can see a lot of cooking shows, food advertisements and pictures of food posted by influencers on social media, which can lead to “substitute consumption”. The COVID-19 pandemic has also caused us to spend more time on screen time, whereby the mechanism described above can be stronger [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, social media has become the major channel for people to obtain updated information related to COVID-19 and to keep connection with their important others. Consequently, there has been a surge in social media usage during the nation-/city-wide lockdown as reflected in recent literature ( 76 ). This new phenomenon has attracted growing research attention; scholars and practitioners start to rethink about the definition of SNA: “whether this compulsive use of social media is just a ‘phase' and a coping mechanism or an indication of addictive behavior having mental health implications” (( 77 ), p. 1).…”
Section: Discussionmentioning
confidence: 99%